Local Tourism Initiative in an Eastern Himalayan Village: Sustainable Ecotourism or Small-scale Nature Exploitation? - Datta Debajit; Banerji Suranjana (Bulletin of Geography. Socio-Economic Series)
Many famous tourism destinations of the eastern Himalayas have become severely polluted and environmentally vulnerable due to decades of unsustainable mass tourism practices. The recent popularization of the so called 'ecotourism destinations' as alternatives to these degraded sites have raised considerable debate among academia, planners and decision makers regarding community based development and environmental conservation. In this study, the newly initiated tourism ventures of a mountainous village named Silerigaon located in this region were evaluated as a case study through participatory appraisals among tourists and local residents to comprehend whether these ventures could truly be termed as ecotourism initiatives. Results derived from the analyses of the primary data collected through these appraisals showed that although the area possessed pristine natural environment and excellent scenic beauty, lack of proper civic amenities and physical infrastructure was hindering the development of sustainable tourism. Here, tourism activities had notably contributed to the increase in annual savings of community members but these financial gains had not equally transcended to all spheres of sustainable community based development. Till now, the activities have lacked the systematic long-term planning required for sustainable ecotourism and nature conservation. Accordingly, these could not be designated as ecotourism activities in their present orientation and capacity. In this regard, several necessary corrective measures to transform these activities into proper ecotourism ones have been suggested.